Analysis of the Impact of Organizational Culture on the Use of Digital Tax System for MSMEs in Medan City - Junawan; Rangga Lawe; M. Mahdi Saman Alfarizie (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the influence of organizational culture consisting of the dimensions of involvement, consistency, adaptability, and mission on the use of the digital tax system in MSMEs in Medan City. The population of this study is MSME owners and managers in Medan City, with a sample of 50 respondents. The research method uses a quantitative approach with multiple linear regression analysis, classical assumption test, and partial hypothesis test (t-test) and simultaneous (F-test). The results of the study show that partially and simultaneously, the dimensions of organizational culture have a positive and significant effect on the use of digital taxation systems. In conclusion, improving organizational culture can support the effectiveness of the implementation of the digital tax system for MSMEs. This research suggests the need for more intensive socialization and training related to the use of the digital tax system so that MSMEs can more easily adopt it.